Importance of NAB2-STAT6 Fusion in the Diagnosis of Pancreatic Solitary Fibrous Tumor with Hamartoma-Like Features: A Case Report and Review of the Literature - Kei Tanaka; Takashi Kishimoto; Masayuki Ohtsuka; Yukio Nakatani; Masaru Miyazaki (Hindawi Limited, 2015)
We report a case of pancreatic hamartoma-like solitary fibrous tumor which was differentiated from pancreatic hamartoma with the detection of NAB2-STAT6 fusion, a specific mutation for solitary fibrous tumors. A pancreatic well-demarcated solid nodule, 21×17 mm, of 82-year-old man was surgically enucleated. Microscopic findings were close to a pancreatic hamartoma that consisted of sparsely distributed pancreatic ducts and acini in heavily collagenized fibrous stroma. Neither islet nor peripheral nerve existed in the tumor. The fibroblastic cells in the stroma were immune-positive for CD34, CD99, and bcl-2. But these expressions were not decisive in the differentiation between solitary fibrous tumor and pancreatic hamartoma, because CD34 was positive for both tumors, and CD99 and bcl-2 expressions were not elucidated in the previous cases of pancreatic hamartomas. Thus, we evaluated NAB2-STAT6 fusion. The fibroblastic cells were positive for STAT6 and sequencing analysis revealed the gene fusion between NAB2 exon 4 and STAT6 exon 2, with which the final diagnos is of solitary fibrous tumor was achieved. In conclusion, detection of NAB2-STAT6 fusion has a great diagnostic value for pancreatic solitary fibrous tumors with hamartoma-like features.